Here, Kansans Know All The Words To “Home On The Range” - Tom Averill (Symphony in the Flint Hills, 2016)
You’re a true Here, Kansan in direct proportion to your recollection of the verses of “Home on the Range.” And before you read one more word, you should go off by yourself and write down as much of that song as you can remember.
Keywords: Home on the Range; old settler’s reunion; parade; buffalo; deer and the antelope; Solomon river valley; lightning bugs; Yoonmi Nam; SAFETY; Katie Twiss